2020
DOI: 10.1186/s12889-020-08466-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid with cardio-metabolic risk factors and metabolic syndrome in seafarers working on tankers

Abstract: Background: There is still controversy over the clinical interpretation of the association between metabolic syndrome (MetS) and serum uric acid (SUA) levels. Therefore, the aim of this study was to investigate the association of SUA levels with MetS and other cardio-metabolic risk factors (CMRF) in seafarers working on tankers. Methods: This cross-sectional study was conducted in 2015 and included 234 male seafarers working on tankers. The participants were divided into three groups based on the tertiles of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Various studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) have reported a relationship between UA and MetS, supporting the findings of our study. Mahajan et al (7) reports that UA raises blood pressure levels through the stimulation of intracellular oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) have reported a relationship between UA and MetS, supporting the findings of our study. Mahajan et al (7) reports that UA raises blood pressure levels through the stimulation of intracellular oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…UA is formed by the liver, is excreted by kidneys with some production by the intestines (7). Hyperuricemia (above 7.0 mg/dL in men and 6.0 mg/dL in women) has been reported in previous studies (3)(4)(5)(6)(7) to be associated with many of the same biomarkers of MetS and diseases such as diabetes, CVD, and kidney disease. Many studies have suggested hyperuricemia is an established risk factor for MetS, (8-10) while others have not reported a relationship when comparing those with and without Diabetes Mellitus (DM) (11).…”
Section: Introductionmentioning
confidence: 80%
“…We assessed the relationship between SUA and the cardiometabolic phenotype in the current study, and our ndings show increasing mean values of metabolic syndrome factors, including LDL and cholesterol, in a dose-response manner corresponding to the SUA tertiles. These results are similar to the ndings of the studies carried out previously in various countries [16][17][18]. According to our ndings, the prevalence rates of MHO and MUHL were higher in the second and third tertiles compared to the rst tertile, which had the lowest SUA.…”
Section: Discussionsupporting
confidence: 92%
“…One former research found weight, WC, BMI, FBS, TG, TC and LDL levels in high level SUA group were significantly higher than those in low level group. 34 Similarly, in a prospective study, BMI, TG and LDL levels significantly increased in hyperuricemia group. 35 Moreover, our findings indicated that SUA was associated with masses of CFRs.…”
Section: Discussionmentioning
confidence: 88%